Informar y contar comunicación y narración en la escritura periodística de Jorge Carrión - Cavazzino, Valeria (Romanica Silesiana, 2020)
In recent years, due to the rise of cultural productions through different media, an increase in the number of journalistic publications of hybrid texts has been observed, which results from the fusion of the narrative and informative functions. The spaces traditionally devoted to different types of journalistic texts which – apart from those merely informative, may include cultural-related and opinion articles – make possible the appearance of articles which distinguish themselves trough entailing both characteristics. Therefore, this paper analyses two articles written by J. Carrion and published in the Spanish edition of The New York Times in 2018. The articles will be scrutinised in relation to the narrative and essayistic works of the author. We illustrate some characteristics of what is generally referred to as narrative journalism, as defined by Herrscher (2012) and Casals Carro (2005), among others. This will allow us to trace a profile of the author, journalist and writer which is linked to the social environment and of his work.